전압-전류 추이와 자속-차전류 기울기 특성을 이용한 변압기 보호계전기법의 성능 개선 - 朴哲圓(Chul-Won Park); 朴載世(Jae-Sae Park); 鄭然萬(Yun-Man Jung); 河炅在(Kyung-Jae Ha); 申明澈(Myong-Chul Shin) (전기학회 논문지 P권, 53(2), 2004)
Percentage differential characteristic relaying(PDR) has been recognized as the principal basis for power transformer protection. Second harmonic restraint PDR has been widely used for magnetizing inrush in practice. Nowadays, relaying signals can contain 2nd harmonic component to a large extent even in a normal state, and 2nd harmonic ratio indicates a tendency of relative reduction because of the advancement of material. Further, as the power system voltage becomes higher and more underground cables are used, larger 2nd harmonic component in the differential current under internal fault is observed. And then, conventional 2nd harmonic restraint PDR exposes some doubt in reliability. It is, therefore, necessary to develop a new algorithm for performance improvement of conventional protective relaying. This paper proposes an advanced protective relaying algorithm by using voltage-current trend and flux-differential current slope characteristic. To evaluate the performance of the proposed algorithm, we have made comparative studies of PDR, fuzzy relaying and DWT relaying. The paper is constructed power system model including power transformer, utilizing the WatATP, and data collection is made through simulation of various internal faults and inrush. As the results of test, the new proposed algorithm was proven to be faster and more reliable.